Neuropathic pain in HIV patients receiving ART without stavudine in an Indonesia Referral Hospital - Octaviana, F.; Safri, A.; Setiawan, D.; Estiasari, R.; Imran, D.; Ranakusuma, T.; Price, Patricia (Elsevier, 2019)
Lower limb neuropathic pain in HIV patients is a common manifestation of sensory neuropathy (HIV-SN), but can be seen in patients who do not meet standard definitions of HIV-SN. The drug stavudine is a risk factor for HIV-SN, but some patients treated without stavudine experience HIV-SN, and the prevalence and risk factors influencing neuropathic pain in this setting are unknown. A cross sectional study at Cipto Mangunkusumo Hospital Jakarta tested 197 HIV patients treated for >12 months without stavudine. HIV-SN was defined using the AIDS Clinical Trial Group Brief Peripheral Neuropathy Screening Test (ACTG-BPNST). A validated Indonesia translation of Douleur Neuropathique en 4 (DN4) questionnaire was used to assess lower limb neuropathic pain. Nerve conduction studies assessed large nerve fiber function and Stimulated Skin Wrinkle (SSW) tests were performed to assess small nerve fibers. The prevalence of neuropathic pain was 6.6%. BPNST + HIV-SN was diagnosed in 14.2% of the cohort and 38.5% of patients with pain. Use of protease inhibitors and ART duration <2 years associated with neuropathic pain in univariate (p =.036, p =.002, resp.) and multivariable analyses (model p <.001). SSW tests were abnormal in 53.8% of subjects with neuropathic pain and only 25.5% without pain (p =.05). Patients with pain without BPNST + HIV-SN had begun ART more recently than those with both diagnoses. Overall this preliminary study showed that neuropathic pain associated with protease inhibitors and a shorter duration of ART in Indonesian HIV patients, and may be an early symptom of small fiber neuropathy in this context.